ChemInform Abstract: Fast Reductive Amination by Transfer Hydrogenation "on Water". Issue 33 (25th July 2013) - Lei, Qian; Wei, Yawen; Talwar, Dinesh; Wang, Chao; Xue, Dong; Xiao, Jianliang
Abstract The title reaction proceeds in a heterogeneous manner and allows unprecedentedly high substrate/catalyst (S/C) ratio.